Reactive events at the graphene oxide–water interface. Issue 88 (22nd October 2021) - David, Rolf; Kumar, Revati
Abstract : The species formed at the graphene oxide–water interface. Abstract : Graphene oxide exhibits interesting reactive events at its interface with water, with water as an active participant. The reactive events are influenced by the level of oxidation of the graphene oxide sheet. The fully oxidized sheet tends to make the interfacial water media acidic leaving the sheet negatively charged, whereas the reduced sheet can form comparatively long lived carbocations as well as split water forming two alcohol groups on the sheet.